1988
DOI: 10.1126/science.3122323
|View full text |Cite
|
Sign up to set email alerts
|

The Primary Structure and Heterogeneity of Tau Protein from Mouse Brain

Abstract: Tau protein is a family of microtubule binding proteins, heterogeneous in molecular weight, that are induced during neurite outgrowth and are found prominently in neurofibrillary tangles in Alzheimer's disease. The predicted amino acid sequences of two forms of tau protein from mouse brain were determined from complementary DNA clones. These forms are identical in their amino-terminal sequences but differ in their carboxyl-terminal domains. Both proteins contain repeated sequences that may be tubulin binding s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
476
1
1

Year Published

1989
1989
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 674 publications
(487 citation statements)
references
References 29 publications
9
476
1
1
Order By: Relevance
“…proportion of each band was found, while for differentiated cells a larger proportion was observed for the slower migrating band. The previous result is compatible with the presence of two cDNA populations; one containing three tubulin-binding regions (the faster migrating band), and the other containing an extra fourth tubulin-binding motif (the slower migrating band) [9,. MU…”
Section: Protein Prepnfariou Blustorna Cellssupporting
confidence: 69%
See 1 more Smart Citation
“…proportion of each band was found, while for differentiated cells a larger proportion was observed for the slower migrating band. The previous result is compatible with the presence of two cDNA populations; one containing three tubulin-binding regions (the faster migrating band), and the other containing an extra fourth tubulin-binding motif (the slower migrating band) [9,. MU…”
Section: Protein Prepnfariou Blustorna Cellssupporting
confidence: 69%
“…By Western blot analyses, using a whole cell protein extract, it was found that the 64 kDa protein reacts against an anti-tau antibody (7.51) which recognizes a region close to the carboxy-terminus of brain tau [37] (Fig. 3), and with a polyclonal antibody ;igainst mu, raised against a pcptide included in the second tubulin-binding motif [9] of brain tau (not shown). Additionally, in the case of differentiated neuroblastoma cells, the 100 kDa protein reacted with antitau antibodies.…”
Section: Protein Prepnfariou Blustorna Cellsmentioning
confidence: 99%
“…8,9 Due to its content of hydrophilic residues, tau is a highly soluble protein. 10 It represents a prototype of the class of natively unfolded (or intrinsically unstructured) proteins. 11 Six isoforms of tau are expressed in the adult human CNS by alternative splicing of exons 2, 3, and 10 of the single MAPT gene (alias TAU) on chromosome 17q21.3; MAPT comprises 16 exons (FIG.…”
Section: Cell Biology and Function Of Taumentioning
confidence: 99%
“…1A). 10,13 Tau-microtubule binding is mediated by the repeat domain and requires the presence of both N-and C-terminally flanking proline-rich domains which target tau to the microtubule surface. 14 The number of repeats can modulate tau-microtubule affinity.…”
Section: Cell Biology and Function Of Taumentioning
confidence: 99%
“…For example, FUS, TDP‐43, and hnRNPA1 contain “prion‐like” LCDs that drive their phase separation. However, in the case of tau, no typical low complexity domain (LCD) exists in the protein sequence, but the intrinsic disorder and the inhomogeneous charge distribution of full‐length tau (Lee et al , 1988) led us to postulate that tau may undergo a similar phase separation. In fact, recent reports using recombinant tau constructs support the argument that tau, despite having no defined LCDs, can undergo LLPS facilitated by crowding agents or RNA in vitro (Ambadipudi et al , 2017; Hernandez‐Vega et al, 2017; Zhang et al , 2017).…”
Section: Introductionmentioning
confidence: 99%